Construction of pcDNA3.1 Vector Encoding RpfD Gene of Mycobacterium tuberculosis - Rakhmawati, Aprilia; Rukmana, Andriansjah; Karuniawati, Anis (Makara Journal of Science, 2018)
Tuberculosis (TB) is an infectious diseasecaused by Mycobacterium tuberculosis (M. tuberculosis). TB is still a major health problem. The Bacillus Calmette-Guérin (BCG) vaccineis the only one available for TB and is known to confer variable levels of protection. Because of thisvariability, a new vaccine is needed to control TB. Proteins secreted by M.tuberculosisare known to induce protective immunity. Within the genome of M. tuberculosis, there is a family of proteins called resuscitation promoting factor (Rpf), which playsa role in the reactivation of M. tuberculosis. RpfD is amember of the Rpf family that has been shown to be immunogenic, makingitsuitable for use as a TB vaccine. The rpfD gene of the M. tuberculosis Beijing strain from the bacterial stock of the Department of Microbiologyat the Medical Facultyof theUniversitas Indonesia was amplified using polymerase chain reaction (PCR) and then insertedintothemammalian expression vector pcDNA3.1(+). Then, the pcDNA3.1(+)-rpfD vector was transformed to Escherichia coli DH5α. A 465-bp target fragment was obtained, and the accuracy ofthecloning was confirmed using colony PCR, restriction enzyme digestion, and sequencing. We expect that this recombinant plasmid will induce immunity in future animal models and thus will prove itself to be a candidate for an M. tuberculosis vaccine.